Racial and ethnic differences in the health of older Americans - Martin, Linda G., 1947-; Soldo, Beth J. (National Academy Press, 1997)
Older Americans, even the oldest, can now expect to live years longer than those who reached the same ages even a few decades ago. Although survival has improved for all racial and ethnic groups, strong differences persist, both in life expectancy and in the causes of disability and death at older ages. This volume examines trends in mortality rates and selected causes of disability (cardiovascular disease, dementia) for older people of different racial and ethnic groups.
Revised versions of some of the papers originally presented at a workshop held Dec. 1994 in Washington.
Keywords: Minority older people -- Health and hygiene -- United States.; Minority older people -- Diseases -- United States.; Older people.; Race.; Ethnic groups.; Aged; Health Status; Racial Groups; Socioeconomic Factors; Ethnicity; Aged, 80 and over; United States; Personnes âgées issues des minorités -- Santé et hygiène -- États-Unis.; Personnes âgées issues des minorités -- Maladies -- États-Unis.; Personnes âgées.; Groupes ethniques.; elderly.; ethnic groups.; race (group of people); MEDICAL -- Preventive Medicine.; HEALTH & FITNESS -- Healthy Living.; HEALTH & FITNESS -- Reference.; HEALTH & FITNESS -- Holism.; Race; Older people; Ethnic groups; Gezondheid.; Ouderen.; Etnische minderheden.; Electronic books.; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings.; Actes de congrès.